Critical loads and exceedances for nitrogen and sulfur atmospheric deposition in Great Smoky Mountains National Park, United States. Issue 10 (6th October 2016) - Fakhraei, Habibollah; Driscoll, Charles T.; Renfro, James R.; Kulp, Matt A.; Blett, Tamara F.; Brewer, Patricia F.; Schwartz, John S.
Abstract: Acid deposition has impacted sensitive streams, reducing the amount of habitat available for fish survival in the Great Smoky Mountains National Park (GRSM) and portions of the surrounding Southern Appalachian Mountains by decreasing pH and acid neutralizing capacity (ANC) and mobilizing aluminum dissolved from soil. Land managers need to understand whether streams can recover from the elevated acid deposition and sustain the healthy aquatic biota, and if so, how long it would take to achieve this condition. We used a dynamic biogeochemical model, PnET‐BGC, to evaluate past, current, and potential future changes in soil and water chemistry of watersheds of the GRSM in response to the projected changes in acid deposition. The model was parameterized with soil, vegetation, and stream observations for 30 stream watersheds in the GRSM. Using model results, the level of atmospheric deposition (known as a "critical load") above which harmful ecosystem effects (defined here as modeled stream ANC below a defined target) occur was determined for the 30 study watersheds. In spite of the recent marked decreases in atmospheric sulfur and nitrate deposition, our results suggest that stream recovery has been limited and delayed due to the high sulfate adsorption capacity of soils in the park resulting in a long lag time for recovery of soil chemistry to occur. Model simulations suggest that over the long term, increases in modeled stream ANC per unit decrease in NH4 + deposition are greater than unit decreases in SO4 2− or NO3 − deposition, due to high SO4 2− adsorption capacity and the limited N retention of the watersheds. Watershed simulations were used to extrapolate the critical load results to 387 monitored stream sites throughout the park and depict the spatial pattern of atmospheric deposition exceedances. These types of model simulations inform park managers on the amount of air quality improvement needed to meet the stream restoration goals.